2011
DOI: 10.1177/0273475311410853
|View full text |Cite
|
Sign up to set email alerts
|

Placing a Hand in the Fire

Abstract: The goal of this study is to evaluate the effectiveness of an experiential learning social media project that was integrated into a graduate marketing class. As part of the semester-long project, students were required to work within a team and create a spoof video, which was posted on YouTube. Students' success was partially determined by the number of views made of the particular video. After reviewing the results obtained by a semistructured survey, the research indicates that the inclusion of an experienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 74 publications
(92 reference statements)
0
11
0
Order By: Relevance
“…Digital oratory is a combination of conventional public speaking or oratory and digital platforms and tools. YouTube is a prominent platform for digital oratory (Payne et al, 2011). Researchers found that a good number of European (Bonsón et al, 2014) and Spanish companies ( Costa-Sánchez, 2017) are using the YouTube platform for promotional activities and customer engagement.…”
Section: Digital Oratorymentioning
confidence: 99%
“…Digital oratory is a combination of conventional public speaking or oratory and digital platforms and tools. YouTube is a prominent platform for digital oratory (Payne et al, 2011). Researchers found that a good number of European (Bonsón et al, 2014) and Spanish companies ( Costa-Sánchez, 2017) are using the YouTube platform for promotional activities and customer engagement.…”
Section: Digital Oratorymentioning
confidence: 99%
“…Furthermore, this integration promotes the learning of technical and theoretical knowledge related to consumer-generated advertising and virtual viral marketing. Results and implications are discussed (Payne et al, 2011)students were required to work within a team and create a spoof video, which was posted on YouTube. Students' success was partially determined by the number of views made of the particular video.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Experiential learning enables more effective learning in the classroom (Granitz & Koernig, 2011;Hamer, 2000;Li, Greenberg, & Nicholls, 2007). Previous teaching innovations have adopted experiential learning tactics for digital marketing topics such as social media (Bacile, 2013), search engine optimization (Clarke & Clarke, 2014), and user-generated content (Payne, Campbell, Bal, & Piercy, 2011). However, there are limited resources for online advertising (Beard & Yang, 2011;Neale et al, 2009), specifically native advertising.…”
Section: Learning Objectivesmentioning
confidence: 99%